CFD Study on Aerodynamic Effects of a Rear Spoiler on Mitsubishi Lancer 2005 - Man, Muhammad Salihin (Progress in Engineering Application and Technology, 2022)
The movement of air around a moving vehicle affects all of its components in some way. Spoilers are typically found on sedans. As a result, by preventing flow separation, the rear spoiler decreases drag. This paper objectives to design an aerodynamic spoiler and to study the effect of spoiler on drag and lift coefficient using Ansys. The flow shift measured for three different height (106mm, 116mm and 126mm) and three different angles (0o, 6o and 12o). The process for analyzing the influence of a spoiler on a vehicle is described using the ANSYS Fluent 19.2 software to do Computational Fluid Dynamics (CFD). According to the flow analysis, the addition of a spoiler virtually reduced the recirculation zone above the rear window, and flow separation was avoided. In the case of passenger vehicles, having more negative force rather than less drag may be more important, as safety is always the main priority. It’s crucial to remember that the benefits of a rear spoiler are typically felt only at high speeds. In most cases, a spoiler will have a negative impact on a car’s performance, especially at low speeds. The original suggestion for this research is to design the entire vehicle, including the side mirror, door handle, and four wheels. These three elements are equally important when compared to a real vehicle because they can alter the quantitative and qualitative behavior of aerodynamics.